What Is Value and How Is It Managed?. (November 2017) - Hallberg, Niklas L.
Abstract: The meaning of the notion of value, as well as associated concepts such as value creation and value appropriation, has been subject to much confusion in marketing and management. This article builds on a rich tradition in economics to untangle some of the ambiguities surrounding these concepts. First, it is argued that a rigorous approach to analyzing value must be based on a subjectivist notion of value related to the perceived needs and preferences of consumers. Second, it is suggested that the value-price-cost (VPC) framework in economics may constitute an effective, yet simple, model for understanding how value is created and appropriated by different actors. Third, it is argued that multilevel issues related to buyer-supplier relationships, stakeholder management and the formation of firms should be addressed using a symmetrical model that allows for freeform bargaining between the involved actors. The article closes with implications for specific debates in management.